Self-esteem in learning disabled children : the role of social competence - Austin Milne, Tamara Helen. (My University, 1995)
This study compared the self-esteem of a group of twenty-one socially and behaviourally competent learning disabled (LD) children, aged 8-12, with that of a group of fifteen socially and behaviourally competent normally achieving (NA) children. Measures used were the Self-Perception Profile for Learning Disabled Students (SPPLDS) and the Social Support Scale for Children (SSSC). The hypotheses that the two groups would not differ in the SPPLDS domains of Social Acceptance and Global Self-Esteem were supported. The hypothesis that the LD children would rate themselves lower in the academic domains was partially supported, as the LD students gave themselves lower scores than did the NA group in Reading and Spelling, but not in Math. The SPPLDS domain of Physical Appearance correlated strongly with self-esteem for both groups, as did the SSSC domain of Classmate Support. Overall, these socially competent LD children were remarkably similar to their NA counterparts in self-esteem, selfperceived competencies, and sources of social support, differing mainly in academic self-concept and abilities.
Keywords: Learning disabled children; Self-esteem in children; Social skills in children